Complex model for distinguishing radio signals - Максименко, Г. А. (Proceedings of National Aviation University (archive), 2000)
Under condition of complete apriori uncertainty, when the main radio signals parameters are unknown it is difficult to synthesize necessary algorithm of finding signals with required characteristics by traditional methods. One of the ways of overcoming the obstacle is modulation of searching process and finding signals by theoretical methods of image discrimination. Considered is a complex model of revealing radio signals and its work based on conceptions and principles of complicated cybernetics systems of image discrimination